A Monochloro Copper Phthalocyanine Memristor with High‐Temperature Resilience for Electronic Synapse Applications. Issue 5 (23rd December 2020) - Zhou, Jia; Li, Wen; Chen, Ye; Lin, Yen‐Hung; Yi, Mingdong; Li, Jiayu; Qian, Yangzhou; Guo, Yun; Cao, Keyang; Xie, Linghai; Ling, Haifeng; Ren, Zhongjie; et al.
Abstract: Memristors are considered to be one of the most promising device concepts for neuromorphic computing, in particular thanks to their highly tunable resistive states. To realize neuromorphic computing architectures, the assembly of large memristive crossbar arrays is necessary, but is often accompanied by severe heat dispassion. Organic materials can be tailored with on‐demand electronic properties in the context of neuromorphic applications. However, such materials are more susceptible to heat, and detrimental effects such as thermally induced degradation directly lead to failure of device operation. Here, an organic memristive synapse formed of monochloro copper phthalocyanine, which remains operational and capable of memristive switching at temperatures as high as 300 °C in ambient air without any encapsulation, is demonstrated. The change in the electrical conductance is found to be a result of ion movement, closely resembling what takes place in biological neurons. Furthermore, the high viability of this approach is showcased by demonstrating flexible memristors with stable switching behaviors after repeated mechanical bending as well as organic synapses capable of emulating a trainable and reconfigurable memristor array for image information processing. The results set a precedent for thermally resilient organic synapses to impact organic neuromorphic devices in progressing their practicality. Abstract : An organic memristor using small‐molecule monochloro copper phthalocyanine as the active material is developed. The unencapsulated memristive devices exhibit high thermal resilience at 300 °C, good flexibility, and high capability of simulating a variety of functions of biological synapses. This work offers an effective approach toward the implementation of brain–computer interface technology for high‐temperature applications.